Community Information Network - Amudhavalli, A. (DESIDOC Journal of Library & Information Technology, 2003)
This article overviews what community information means and its implications on the role of a library and information centre. No single institution can meet the general information requirements of any given community. It attempts to examine how .a cooperative venture of interagency network can lead to an effective community information service suitable for the local population. http://dx.doi.org/10.14429/dbit.19.1.3456